2011
DOI: 10.1039/c1mb05014a
|View full text |Cite
|
Sign up to set email alerts
|

Relating protein adduction to gene expression changes: a systems approach

Abstract: Modification of proteins by reactive electrophiles such as the 4-hydroxy-2-nonenal (HNE) plays a critical role in oxidant-associated human diseases. However, little is known about protein adduction and the mechanism by which protein damage elicits adaptive effects and toxicity. We developed a systems approach for relating protein adduction to gene expression changes through the integration of protein adduction, gene expression, protein-DNA interaction, and protein-protein interaction data. Using a random walk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…More specifically, in the first step, we utilized the software NetWalker to expand metformin upstream genes and downstream genes for longitudinal conduction [116]. The NetWalker implements the random walk with a starting probability.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, in the first step, we utilized the software NetWalker to expand metformin upstream genes and downstream genes for longitudinal conduction [116]. The NetWalker implements the random walk with a starting probability.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al (44) tried to remove this effect by assessing the statistical significance of the scores. To evaluate whether considering network topology could improve network-based function prediction, we combined two statistic metrics, localP and edgeP, with the rank ratio metric for assessing the significance of the priority scores (see supplemental Text S2).…”
Section: Discussionmentioning
confidence: 99%
“…The final score of a gene in the network was defined by iterating the above equation until ÎŁ i =1 n | p i t +1 − p i t | fell below the predefined threshold of 1 × 10 −6 , as previously described (43, 44). A higher score of a gene represents a closer relationship between the gene and the seed genes.…”
Section: Methodsmentioning
confidence: 99%
“…A systems analysis approach that integrates proteomic and gene expression data revealed that treatment of cells with HNE not only results in modification of CDK2 but also leads to significant decreases in the genes controlled by CDK2 activation. 22 These data suggest that HNE modification of CDK2 could result in cell cycle arrest at the G1/S-phase transition. Here, we show that modification of recombinant CDK2 by HNE disrupts its kinase activity.…”
Section: Introductionmentioning
confidence: 90%